2020
DOI: 10.1002/btpr.2981
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mono‐rhamnolipids and di‐rhamnolipids on microbial enhanced oil recovery (MEOR) applications

Abstract: Rhamnolipids (RMLs) have more effectiveness for specific uses according to their homologue proportions. Thus, the novelty of this work was to compare mono‐RMLs and di‐RMLs physicochemical properties on microbial enhanced oil recovery (MEOR) applications. For this, RML produced by three strains of Pseudomonas aeruginosa containing different homologues proportion were used: a mainly mono‐RMLs producer (mono‐RMLs); a mainly di‐RMLs producer (di‐RMLs), and the other one that produces relatively balanced amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 40 publications
0
7
1
1
Order By: Relevance
“…Hence, for N-acyltyrosine, HAA, and mRL, the CMC derived from VPBO assay matches the range of previously reported values, however, for C 10 -C 10 dRL, it does not. Nevertheless, other studies determined deviating CMCs for dRL (and for mRL as well) varying between 0.05 and 0.23 mg/ml probably dependent on impurities, mixtures, and variations in chain length and degree of saturation (Syldatk et al, 1985;Abalos et al, 2001;Nitschke et al, 2005;Dubeau et al, 2009;Tiso et al, 2017;Rocha et al, 2020). Furthermore, the CMC value depends on temperature, pH, and salt concentration, which may differ from the conditions in the present study (room temperature in LB medium adjusted to pH 7).…”
Section: Discussioncontrasting
confidence: 69%
“…Hence, for N-acyltyrosine, HAA, and mRL, the CMC derived from VPBO assay matches the range of previously reported values, however, for C 10 -C 10 dRL, it does not. Nevertheless, other studies determined deviating CMCs for dRL (and for mRL as well) varying between 0.05 and 0.23 mg/ml probably dependent on impurities, mixtures, and variations in chain length and degree of saturation (Syldatk et al, 1985;Abalos et al, 2001;Nitschke et al, 2005;Dubeau et al, 2009;Tiso et al, 2017;Rocha et al, 2020). Furthermore, the CMC value depends on temperature, pH, and salt concentration, which may differ from the conditions in the present study (room temperature in LB medium adjusted to pH 7).…”
Section: Discussioncontrasting
confidence: 69%
“…Furthermore, the most hydrophobic character of mono-RML was shown as well by the hydrophilic-lipophilic balance (HLB) results in previous work from our group. 21 In this same work, it was shown that the CMC of mono-RML was lower than that of mono/ di-RML and di-RML, respectively. This confirms the best adhesion ability of mono-RML.…”
Section: Contact Angle Analysismentioning
confidence: 84%
“…Rhamnolipids production, quantification and tensoactive parameters, as well as structural analysis of rhamnolipids were previously published in a study from our group about rhamnolipids application on Microbial enhanced oil recovery (MEOR) 21 . Details of the methodology are provided following.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MEOR termasuk kedalam tertiary oil recovery atau kita kenal dengan Enhance Oil Recovery yang teknologi nya berbasis biological dengan metode metabolisme mikroba (biomassa, biopolimer, gas, asam, pelarut, enzym dan karbon aktif) dan aktivitas (metabolisme hidrokarbon, plugging) yang digunakan untuk meminimalisir residu minyak yang tertinggal pada reservoir (Purwasena et al, 2019) 2 . Microbial Enhanced Oil Recovery (MEOR) menjadi teknologi yang sudah mendapatkan visibilitas atas kemampuannya meningkatkan hasil produksi minyak pada dekade terakhir yang menggunakan bakteri atau bio-produk (Rocha et al, 2020).…”
Section: B Microbial Enhanced Oil Recovery (Meor)unclassified